Islamic Economic Transformation in the Digital Era: Opportunities and Challenges - Bella Mauris (Journal of Islamic Economy, 2024)
The digital era has driven significant changes in various economic sectors, including in the development of Islamic economics. This study aims to examine the opportunities and challenges of Islamic economic transformation in the context of digitalization using the Systematic Literature Review (SLR) method. Data were obtained from selected academic literature published between 2019 and 2024, which were then analyzed using thematic coding techniques. The results of the study indicate that digitalization offers great opportunities to increase Islamic financial inclusion, expand market reach, and introduce innovations such as Islamic fintech, blockchain, and waqf-based crowdfunding. However, a number of challenges have emerged, such as regulatory uncertainty, low Islamic digital financial literacy, and cybersecurity risks. This study concludes that the success of Islamic economic transformation in the digital era is highly dependent on the synergy between adaptive regulations, technological innovations that are in accordance with Islamic principles, and increasing digital literacy among Muslim communities. These findings are expected to be the basis for developing strategies to strengthen the Islamic economy in facing the dynamics of the digital-based global economy.